Respuesta :
What's the difference between A) and C)??
There should be an E) because the correct answer would be in either of these forms:
[tex] {DE}^{2} = {(4 - 1)}^{2} + {(1 - 3)}^{2} \: \: or \\ DE = \sqrt{( {3}^{2} + {2}^{2} )} \: \: or \\ {DE}^{2} = {(4 - 1)}^{2} + {(3 - 1)}^{2} [/tex]
There should be an E) because the correct answer would be in either of these forms:
[tex] {DE}^{2} = {(4 - 1)}^{2} + {(1 - 3)}^{2} \: \: or \\ DE = \sqrt{( {3}^{2} + {2}^{2} )} \: \: or \\ {DE}^{2} = {(4 - 1)}^{2} + {(3 - 1)}^{2} [/tex]
the answer is
C) DE = (4 - 1)2 + (1 - 3)2
rewriten
DE = sqrt (4 - 1)^2 + (1 - 3)^2
C) DE = (4 - 1)2 + (1 - 3)2
rewriten
DE = sqrt (4 - 1)^2 + (1 - 3)^2